الاستغراب: مفهومه، خلفياته، أهدافه وأهميته - نصيره عماره (University of Eloued جامعة الوادي, 2023)
يرى بعض الباحثين أن الاستغراب مجرد بحث أو دراسة عن حالة الغرب، من حيث أنه مجتمع متفسخ ومنحل أخلاقياً، علينا بالحذر منه، غير أنه تحول إلى ماهية يجب دراسته بعناية فائقة من كل النواحي، ومن هنا كان هدفنا هو أن نجلّي حقيقة الاستغراب. وقبل تحقيق الهدف لابد أن نطرح الإشكالية. فما هو الاستغراب؟ وللإجابة عن تلك الإشكالية جعلتنا نتبع منهج معين، وهو الدراسة الوصفية والمقارنة، مع المنهج التحليلي، لنصل إلى نتيجة وهي أن الاستغراب يشكّل حالة استثنائية في هذا العصر اتجاه العالم العربي والإسلامي، علينا بتعميق دراسته، ببيان مفهومه، ومدى ضرورته لنا في حاضرنا ومستقبلنا، فالغرب الفكري والسياسي والديني والعلمي لا يريد منا معرفته على حقيقته ومقاصده اتجاهنا، لذا يحاول صدنا وإضعاف رؤيتنا له، مما يتوجب علينا الاطلاع على تاريخه ومنظومته الفكرية والأخلاقية، ومن ذاك تظهر لنا أهمية الاستغراب، كما علينا الحذر مما يصل إلينا مما يتنافى مع قيمنا وهويتنا؛ لأنه يمثل قيماً حضارية تختلف في الكثير منها على قيمنا الروحية والأخلاقية والاجتماعية، دون أن نغفل عن معارفه وإنجازاته المادية والطبيعية والتكنولوجية والمعلوماتية المفيدة لنا في حياتنا اليومية. : Abstract Some researchers believe that Occidentalism is merely research or study on the state of the West, In that it is a corrupt and morally decadent society, We have to be careful of him, However, it has become an essence that must be studied very carefully in all aspects, Hence, our goal was to clarify the truth of Occidentalism, Before achieving the goal, we must raise the problem, What is Occidentalism? To answer this problem, we followed a specific approach, It is a descriptive comparative study, With the analytical approach, Let us reach the conclusion that Occidentalism constitutes an exceptional case in this era regarding the Arab and Islamic world, We must deepen its study, Explaining his concept, And how necessary it is for us in our present and future, The intellectual, political, religious and scientific West does not want us to know it for what it really is and its goals towards us, so it tries to repel us and weaken our vision of it, Therefore, we must look at its history and its intellectual and moral system, From this, the importance of strangeness becomes apparent to us, and that we must be careful of what reaches us that is inconsistent with our values and identity, ecause it represents civilizational values, many of which differ from our spiritual, moral and social values, thout losing sight of his knowledge and material, natural, technological and informational achievements that are useful to us in our daily lives.
Occidentalism: Its Concept, Backgrounds, Goals And Importance
Keywords: الاستغراب؛ الغرب؛ العالم العربي؛ المقارنة.; the West; the Arab world; the Comparison.; The Occidentalism